2012
DOI: 10.1111/j.1365-2125.2012.04335.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of single dose (R)‐ and (S)‐warfarin administered separately and together: relationship to VKORC1 genotype

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The contribution of (S)-warfarin to the clinical effect of rac-warfarin is well understood. The extent to which (R)-warfarin contributes to the clinical effect of rac-warfarin is unclear. WHAT THIS STUDY ADDS• Using unequivocally pure (R)-and (S)-warfarin we have demonstrated that (R)-warfarin contributes to the hypoprothrombinaemic effect of single large doses of warfarin.• The extent of the interaction is dependent on VKORC1 genotype. AIMS1) To determine the pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
5
33
1
1
Order By: Relevance
“…Binding Site-1 shows selectivity for S-warfarin (Fig. 2b), although the ability of R-warfarin to also bind at this site (Table 1) is in agreement with the recent data of Maddison et al [30], who reported that R-warfarin contributes toward the anticoagulant response generated by a single dose of racwarfarin. Binding Site-2 binds both warfarin enantiomers with similar affinity ( Table 1).…”
Section: Resultssupporting
confidence: 88%
“…Binding Site-1 shows selectivity for S-warfarin (Fig. 2b), although the ability of R-warfarin to also bind at this site (Table 1) is in agreement with the recent data of Maddison et al [30], who reported that R-warfarin contributes toward the anticoagulant response generated by a single dose of racwarfarin. Binding Site-2 binds both warfarin enantiomers with similar affinity ( Table 1).…”
Section: Resultssupporting
confidence: 88%
“…CYP2C9, a polymorphic enzyme, is the principal form of human liver CYP450 that modulates the in vivo anticoagulant activity of warfarin . S warfarin is about twofold more active than R warfarin, but is eliminated more rapidly . The clearance of R warfarin is generally half that of S warfarin, thus as the volumes of distribution are similar, the half‐life of R warfarin is longer than that of S warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled HLMs (0.1 mg/ml) or recombinant enzymes (40 pmol/ml) were incubated with (S)-warfarin (2.5 mM) in the presence of noscapine (0-100 mM) in a NADPH-regenerating system for 20 minutes. The warfarin concentration was selected based on the apparent K m values in pooled HLMs or cDNA-expressed CYP2C9 (2-9 mM) (Liu et al, 2012) and the clinically relevant concentration range (C max , ;5 mM) (Maddison et al, 2013). 7-Hydroxywarfarin formation rates were determined, and the half-maximal inhibitory concentration (IC 50 ) values were estimated.…”
Section: Methodsmentioning
confidence: 99%